Journal of Remanufacturing - Ijomah, Winifred L.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer.)
The Journal of Remanufacturing aims to establish an effective channel of communication between academic and research institutions, industry and persons concerned with the challenges and significance of remanufacturing. The international dimension is emphasized in order to overcome cultural and national barriers and to meet the needs of global sustainability given the significant adverse ecological impacts of accelerating global industrialization. The journal's focus is to propose and foster discussion that would assist: The establishment of the intellectual foundation and direction for the longer-term development of remanufacturing research. Step changes in remanufacturing knowledge via holistic, interdisciplinary research that fuses academic and industrial expertise. Communication of practice and research developments to enable industry to use remanufacturing to address competitive, environmental and legislative pressures.
Keywords: Business; Management science; Engineering; Environmental management; Waste management; Sustainable development; Engineering, general; Sustainable Development; Waste Management/Waste Technology; Business and Management, general; Environmental Management